DIGITAL RIGHT MANAGEMENT (DRM) MENGGUNAKAN METODE DES DAN BLOWFISH UNTUK KEAMANAN AUDIO - Anggitha Septia Liana (2023)
DRM (Digital Right Management) it self is a system that can protect digital electronics or digital audio from copyright as user restrictions. Data security is indeed very sentitive, especially with regard to the confidentiality of the data, especially audio data, because many people download audio at random which results in a lot of misuse by irresponsible parties. The research was conducted to implement DRM using the DES and Blowfish methods so that it can proecue encrypted and decryptable audio. This application aims to protect an audio that is carried out throught the encryption process and the decryption process. The audio that has been encryption and decrypted has not changed, so the sample rate is the same, namely 441000, the only difference being the length of the encryption. The test result show that the encryption process can be downloaded but the audio cannotbe played mush have a key or key that goes through the decryption process, because this DRM has user limits, and the decryption process can be download sothat it canbe played and the audio quality in the trial does not have a change in quality.